APLIKASI ELECTRONIC COMMERCE SEBAGAI MEDIA PENJUALAN PRODUK MAKANAN RINGAN BUSINESS DEVELOPMENT CENTER KABUPATEN PRINGSEWU - Adi Prsetia Nanda; Anggi Maharani (LPPM STMIK Pringsewu, 2018)
The rapid technological developments directly or indirectly affect the trading system. Currently, just by accessing E-Commerce via the Internet only, we can choose the desired goods, know the details of the goods, and can conduct transactions with anyone without being limited by time and distance. Because of the lack of information containers that limit the seller and the consumer, so I think to make this website to be used as a transaction place selling snack product. This application is made using the programming language PHP, HTML and MySQL. Software used to create this application using Macromedia Dreamweaver CS4 and XAMPP. system development method using waterfall method. The purpose of this research is to build E-commerce website as a medium of online.